SYSTEMATIC OF EXPERT SYSTEM BASE ON SOFTWARE AND CALCULATION METHOD - Yunanri W; Doddy Teguh Yuwono; Ika Safitri Windarti (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
The expert system is a system that seeks to adopt human knowledge into technology, so that technology can solve problems as is usually done by experts. A good expert system is designed to solve a particular problem by imitating the work of the experts. With expert systems, the layman can solve quite complicated problems, because in fact the problem can only be solved with the help of experts. For experts, the expert system will also assist its activities as a highly experienced assistant. Currently there are many studies that raise cases about expert systems. This study aims to create systematic on expert systems based on a collection of expert system cases and classify them based on the tools used, implementation types and frequently used methods.